Patient-Tailored, Imaging-Guided, Long-Term Temozolomide Chemotherapy in Patients with Glioblastoma - Norbert Galldiks; Lutz W. Kracht; Lothar Burghaus; Roland T. Ullrich; Heiko Backes; Anna Brunn; Wolf-Dieter Heiss; Andreas H. Jacobs (Molecular Imaging)
We present two patients with glioblastoma with an unusually stable clinical course and long-term survival who were treated after surgery and radiotherapy with adjuvant temozolomide (TMZ) chemotherapy for 17 and 20 cycles, respectively. Afterward, adjuvant TMZ chemotherapy was discontinued in one patient and the dosage of TMZ was reduced in the other. In addition to clinical status and magnetic resonance imaging, the biologic activity of the tumors was monitored by repeated methyl- 11 C-l-methionine (MET) and 3′-deoxy-3′- 18 F-fluorothymidine (FLT) positron emission tomography (PET) studies in these patients. In these patients, repeated MET-and FLT-PET imaging documented complete response to the initial treatment regimen, including resection, radiation, and TMZ, and during the course of the disease, recurrent, uncontrollable tumor activity. Continuation or dose escalation of TMZ in both patients was shown to be ineffective to overcome the metabolic activity of the tumor. Our data suggest that repeated MET- and FLT-PET imaging provide information on the biologic activity of a tumor that is highly useful to monitor and detect changes in activity.